Choice of respiratory therapy in severe patients with new coronavirus infection COVID-19 - Boltayev Elmurod Bekmurod ugli (Genius Journals, 2023)
The respiratory problems of pneumonia and acute respiratory distress syndrome (ARDS) caused by COVID-19 coronavirus infection have not yet been fully resolved. World medicine has extensive experience in the use of nasal tube oxygen therapy, high-flow oxygen therapy (HFOT), non-invasive pulmonary ventilation (NIPV) and invasive pulmonary ventilation (IPV) in patients. However, the problem of choosing non-invasive pulmonary ventilation or invasive pulmonary ventilation in patients has not been fully resolved. This is because the effectiveness of non-invasive pulmonary ventilation is higher than that of invasive pulmonary ventilation, which prevents the solution of this problem. Below we attempt to shed more light on the selection of an effective method of respiratory therapy based on simple respiratory indications. Objective: To study the choice of respiratory therapy in severe patients with new coronavirus infection COVID-19.
Keywords: Oxygen therapy; high flow oxygen therapy